UTILIZATION OF THE INAPORTNET SYSTEM FOR SIMKIM DEVELOPMENT TO IMPROVE SERVICE IN IMMIGRATION EXAMINATION FIELDS IN TPI LAUT - Muhammad Risyad (TEMATICS: Technology ManagemenT and Informatics Research Journals, 2020)
In the provision of public services, the standard of immigration services is an essential element as well as a form of effort to protect the sovereignty of the Indonesian State. Public facilities at control points for maritime immigration (TPI) tend to be involved and erratic. Data collection and monitoring of foreign ships and members of the crew is also conventionally carried out. The existence of Inapornet (Indonesia Port Integration System) which was initiated by the Ministry of Transportation has been implemented to help improve the performance of port authorities in the field of public services because as the basis of a system, it helps change conventional traditions to become modern with the help of information communication technology. The Inaportnet system itself is able to speed up the port clearance process. However, until now the Inaportnet system has not been applied by the Directorate General of Immigration. Then the research was carried out using a qualitative research methodology with a qualitative - descriptive method to analyze the implementation of the Inapornet system as a whole. All data obtained were obtained from the Immigration Office class I TPI Tanjung Priok. The results showed that the use of the Inaportnet system can be the fastest and easiest solution at this time to overcome the lack of support for technology and information systems that were created specifically to address and fulfill services in the field of immigration inspection at marine TPI. The application of this system supports the movement of the central government in implementing a one gate away system at ports.